The Effect of Public Service Motivation, Meaningful Work and Work Engagement on Employee Performance in The Public Sector - Erwis Ade Juliana Nababan; Putri Mega Desiana (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
Employees are the key to organizational success that play a significant role in organizational performance, where higher individual employee performance is the basis for higher organizational performance. There are several factors that affect the performance of employees in the public sector, and in this research the analyzed factors that affect employee performance are public service motivation, meaningful work and work engagement. The research method used is a quantitative approach, with a total of 209 employees working at the Inspectorate General of the Ministry of Health. Then the data was processed using SPSS and Structural Equation Modeling (SEM) LISREL 8.8. The results show that public service motivation, meaningful work and work engagement have a positive and significant effect on employee performance, and there is a role for work engagement that mediates the effect of public service motivation and meaningful work on employee performance.